Molluscicidal activity of Solanum elaeagnifolium seeds against Galba truncatula intermediate host of Fasciola hepatica: Identification of β-solamarine. (2nd April 2016) - Njeh, Fatma; Feki, Houda; Koubaa, Imed; Hamed, Nejia; Damak, Mohamed; Ayadi, Ali; Hammami, Hayet; Mezghani-Jarraya, Raoudha
Abstract: Context : The persistence of fascioliasis in many developing countries urges the search for simple, cheap, and effective substances. In this view, plants provide interesting molluscicidal activities thanks to the secondary metabolites they produce. The genus Solanum is known for its potent effect on vector snails. Objective : The molluscicidal activity of Solanum elaeagnifolium Cav. (Solanaceae) seeds against Galba truncatula Müll. (Lymnaeidae), intermediate host of Fasciola hepatica L. (Fasciolidae), was evaluated. Materials and methods : Solanum elaeagnifolium seeds were powdered and successively extracted using n -hexane, methylene chloride, acetone, and methanol, for 20 h each. After filtration, solvents were evaporated. An acid–base treatment was conducted on seed methanolic extract to isolate total alkaloids and β-solamarine. Total saponins fraction was obtained after successive macerations and evaporations. The molluscicidal activity was evaluated by subjecting snails, in groups of 10, for 48 h to 500 mL of extracts, fractions, and pure product aqueous solutions, each containing amounts, ranging from 1 to 50 mg of plant material in 5 mg increments. Results : The methanolic extract of seeds, β-solamarine isolated for the first time from this plant and total saponins fraction showed very potent activities on snails, giving respective median lethal concentrations (LC50 ) of 1.18, 0.49, and 0.94 mg/L. Total alkaloids fraction obtained from the methanolic extract was less active giving an LC50 value of 14.67 mg/L. Discussion and conclusion : This study emphasizes that glycoalkaloids and saponins of Solanum elaeagnifolium are potent molluscicidal agents. Seed methanolic extract, β-solamarine, and total saponins fraction may be used as molluscicides.